Pesquisa de vírus entéricos e indicadores bacterianos de poluição fecal na água e no sedimento em área de manguezal da Baía de Vitória (ES) - Martins, Sara Angelino (2013)
The region of the Ilha das Caieiras, in Vitória (ES) is located within an estuarine region in Vitoria Bay and is close to an extensive mangrove area. The resident population ratio remains highly dependent relationship on natural resources offered (oysters, clams) therefore used as a source of subsistence and recreation. The mangrove of Ilha das Caieiras receives sewage from adjacent areas, contaminating water and shellfish therein. In addition, microorganisms that are cast together with the sewage in the coastal environment can be accumulated in the sediment. This objective of this work was to investigate enteric viruses and bacterial indicators of fecal pollution in the sediment and water at three points of this estuary (P1, P2 and P3) mangrove area over 15 months of monitoring. We evaluated a total of 45 samples for the presence of thermotolerant coliform (TC), enterococci and enteric viruses (adenovirus - HAdV; rotavirus - RVA, and norovirus - NoV GII, using a nested PCR. We also evaluated the physico-chemical parameters of the water collection point next to the sediment. Microbiological analyzes of the sediment were respectively geometric mean for enterococci: 1.5 x103, 1.5 x103 and 1.1 x103 UFC/100g, thermotolerantes coliforms: 4.9 x103, 2.6 x102 and 5.1 x102. In water samples the results for enterococci were: 7.6 x101, 5.0 x101 and 1.1 x102 and themortolerants coliforms: 2.2 x102, 1.3 x102, and 3.0 x102. Analyses of enteric viruses in water samples showed frequencies of 20% for RV, 13% for AdV and 8.8% for NoV GII and sediment samples only NoV GII (4.5%) was found. The presence of the viral and bacteriological samples indicates that this region is under anthropogenic impact, and that the sediment from the mangrove of Ilha das Caieiras can act as a reservoir of pollutants that are released to the water column can cause gastrointestinal diseases the people who use this area as a source of livelihood and recreation.